PENGEMBANGAN MODUL ELEKTRONIK MENGGUNAKAN FLIP PDF PROFESSIONAL PADA MATERI PENGUKURAN - Chen, Diki; Srimadona, Agus (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This study aimed to determine the results of the development of electronic modules on measurement material and student's perceptions of the product being developed. The type of research conducted is R&D research with the development model selected, namely the 4-D development model. The research samples used were two expert lecturers as product assessors and 25 students as samples whose perceptions were measured. The sampling technique used was purposive sampling, with the instruments used being a student needs questionnaire, material validation, media validation, and student perceptions. The data analysis for the questionnaire is descriptive statistics, while the instrument data validation uses reliability and validity tests. The results of the data obtained indicate that the product is feasible to use and can be accessed using a mobile phone via the link provided by the author, while the perception of the electronic module obtained shows a very good perception. Thus, this module is considered feasible and ready to be used to assist students in understanding.